Cationic amphiphilic dendrons with effective antibacterial performance. Issue 3 (4th January 2022) - Guo, Wei; Wang, Yongjie; Wan, Pengqi; Wang, Hao; Chen, Li; Zhang, Shaokun; Xiao, Chunsheng; Chen, Xuesi
Abstract : We designed and synthesized a series of cationic amphiphilic dendrons with cationic dendrons and hydrophobic alkyl chains, which exhibited rapid and broad-spectrum bactericidal activity. Abstract : Bacterial infections and antibiotic resistance have become a global healthcare crisis. Herein, we designed and synthesized a series of cationic amphiphilic dendrons with cationic dendrons and hydrophobic alkyl chains for potential antibacterial applications. Our results showed that the antimicrobial activities of the cationic amphiphilic dendrons were highly dependent upon the length of the hydrophobic alkyl chain, whereas the number of cationic charges was less important. Among these cationic amphiphilic dendrons, a prime candidate was identified, which possessed excellent antimicrobial activity against various pathogens (minimum inhibitory concentrations of 9, 3, and 3 μg mL −1 for Escherichia coli, Staphylococcus aureus, and methicillin-resistant Staphylococcus aureus, respectively). Scanning electron microscopy and fluorescence microscopy analyses showed that it could disrupt the integrity of a pathogen's membrane, leading to cell lysis and death. In addition, in vitro bacteria-killing kinetics showed that it had rapid bactericidal efficiency. It also had excellent antimicrobial activities against MRSA in vivo and promoted wound healing. In general, the synthesized cationic amphiphilic dendrons, which exhibited rapid and broad-spectrum bactericidal activity, may have great potential in antimicrobial applications.